Clinically meaningful measurement of pain in children with sickle cell disease. Issue 10 (17th June 2013) - Myrvik, Matthew P.; Brandow, Amanda M.; Drendel, Amy L.; Yan, Ke; Hoffmann, Raymond G.; Panepinto, Julie A.
Abstract Background Limited understanding of the interpretability of patient‐reported pain scores may impact pain management. The current study assessed the minimal clinically significant improvement in pain and pain scores signifying patient‐reported need for medication and treatment satisfaction in patients with sickle cell disease (SCD). Procedure Patients, 8–18‐years‐old, with SCD were recruited while receiving treatment for pain. Patients completed initial pain severity ratings using the Visual Analog Scale (VAS) and the Numeric Rating Scale (NRS). Serial assessments of pain severity, pain relief, perceived need for medication, and treatment satisfaction were completed in the emergency department and the hospitalization. Data were used to calculate the minimal clinically significant improvement in pain and pain scores associated with perceived need for pain medication and treatment satisfaction. Results Twenty‐eight patients completed 305 assessments during 37 total visits. A decrease in pain severity score of 0.97 cm for the VAS and 0.9 for the NRS was found to be the minimum clinically significant improvement in pain. Pain scores >7.45 cm on the VAS or 7.5 on the NRS were suggestive of patient‐reported need for pain medication. Pain scores <7.35 cm on the VAS or 8.5 on the NRS were suggestive of patient‐reported treatment satisfaction discrimination. Conclusions The minimal clinical significant improvement was defined for the VAS and NRS and both scales were able to discriminate between important clinical findings including pain relief, need for pain medication, and treatment satisfaction. Collectively, this study provides data to improve our understanding of pain ratings of pediatric patients with SCD. Pediatr Blood Cancer 2013;60:1689–1695. © 2013 Wiley Periodicals, Inc.